Moving beyond the scale: musculoskeletal risks, evidence gaps and emerging combination strategies to optimize the quality of weight loss pharmacotherapy in older adults - Reid, Kieran F.; Bhasin, Shalender (Frontiers in Aging, 2025)
The increasing prevalence of obesity among older adults is a significant clinical and public health challenge. In this population, obesity contributes to numerous chronic diseases, functional decline and elevated mortality. This growing concern highlights the urgent need for more effective weight management strategies for older adults. Pharmacologic treatments, particularly GLP-1 receptor agonists and dual agonists, have emerged as promising treatments for weight loss, but their effects remain understudied in older adults. In this article, we discuss the potential musculoskeletal implications associated with the use of weight loss pharmacotherapy among older adults. We emphasize the consequences of lean mass loss, particularly the loss of skeletal muscle mass, which represents a critical determinant of ambulation, physical function and major regulator of metabolic health in older adults. We also describe the adverse risks of weight regain and weight cycling, and the significance of lean mass preservation during weight loss for older individuals. Finally, we identify knowledge gaps associated with safe and effective obesity pharmacotherapy in older adults and emphasize the potential benefits of combining GLP-1 therapies with promyogenic agents, structured exercise, and targeted nutritional interventions for optimizing weight loss quality in this population. These integrated approaches merit further investigation in clinical trials to determine their synergist effects for enhancing body composition while promoting independence, vitality and wellbeing in older adults undergoing pharmacologic weight loss.